İlkokul Öğrencilerinin Serbest Yazma Etkinliklerindeki Konu Eğilimlerinin İncelenmesi / Investigation of Subject Trends in Primary School Students’ Free Writing Activities - Batur, Zekerya; Tufan, Bitir (Journal of History Culture and Art Research, 2019)
Absract The aim of this study is to determine the tendencies of the students in the free writing activities of primary school (2nd, 3rd and 4th grade) students and place, class level, parents' education status, daily internet usage status, monthly book number of books to determine the number of page variables. The mixed method was used in the study. The paper used in the students' free writing studies was examined by document analysis method and the trends were determined. In addition, the data obtained from the forms that the students stated their demographic characteristics were processed in SPSS 25.0 package program and interpreted with cross-comparison tables and Chi-Square test. The study group consisted of 900 students from the 2nd, 3rd and 4th grades selected from the primary, district and village schools in the 2017-2018 academic year by using the maximum diversity method. In the study, subject trends in the free writing activities of primary school students were determined. According to the data obtained, it was found that the subject trends of the students differ according to the place of residence, class levels, mother and father education status, daily internet usage status and number of book pages they read monthly. Öz Bu çalışmanın amacı, ilkokul (2, 3 ve 4. sınıf) öğrencilerinin serbest yazma etkinliklerindeki konu eğilimlerini belirlemek ve yaşanılan yer, sınıf düzeyi, anne ve baba eğitim durumları, günlük internet kullanım durumları, aylık okudukları kitap sayfa sayıları değişkenleri açısından tespit etmektir. Çalışmada karma yöntem kullanılmıştır. Öğrencilerin serbest yazma çalışmalarında kullandıkları kâğıtlar doküman analizi yöntemiyle incelenerek konu eğilimleri tespit edilmiştir. Ayrıca öğrencilerin demografik özelliklerini belirttikleri formlardan elde edilen veriler SPSS 25.0 paket programına işlenerek çapraz karşılaştırma tabloları ve Ki-Kare testi ile yorumlanmıştır. Araştırmanın çalışma grubunu, 2017-2018 eğitim-öğretim yılında Aydın il merkezi, ilçe ve köy okullarından amaçlı örnekleme çeşitlerinden maksimum çeşitlilik yöntemi ile seçilen 2, 3 ve 4. sınıftan toplam 900 öğrenci oluşturmaktadır. Araştırmada, ilkokul öğrencilerinin serbest yazma etkinliklerindeki konu eğilimleri tespit edilmiştir. Elde edilen veriler doğrultusunda, öğrencilerin konu eğilimlerinin yaşanılan yere, sınıf düzeylerine, anne ve baba eğitim durumlarına, günlük internet kullanım durumlarına ve aylık okudukları kitap sayfa sayılarına göre farklılaştığı saptanmış ve bu farklılığın anlamlı olduğu sonucuna ulaşılmıştır.